2018
DOI: 10.1016/j.cell.2018.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Expression of LincGET Biases Cell Fate in Two-Cell Mouse Embryos

Abstract: Graphical AbstractHighlights d LincGET is asymmetrically expressed in the nucleus of twoto four-cell mouse embryos d LincGET overexpression biases blastomere fate toward inner cell mass (ICM) d LincGET physically binds to CARM1 d LincGET/CARM1 activates ICM-specific genes In BriefAn endogenous retrovirus-associated nuclear long noncoding RNA biases cell fate in mouse two-cell embryos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 40 publications
3
115
0
Order By: Relevance
“…However, we failed to identify either of these two features at TAD borders in X. tropicalis , which could also be caused by the heterogeneity in the cells we used. Recent work revealed that cells could be different at as early as two- to four-cell stages during mouse embryo development 51 . At s9, at least three lineages of cells already exist in X. tropicalis embryos.…”
Section: Discussionmentioning
confidence: 99%
“…However, we failed to identify either of these two features at TAD borders in X. tropicalis , which could also be caused by the heterogeneity in the cells we used. Recent work revealed that cells could be different at as early as two- to four-cell stages during mouse embryo development 51 . At s9, at least three lineages of cells already exist in X. tropicalis embryos.…”
Section: Discussionmentioning
confidence: 99%
“…To further define the transcriptome characteristics of the blastomeres, we performed UHC (19 813 genes) to group the cells from morula. It has been reported that blastomeres with high CARM1 bias the subsequent fate toward ICM, 21,22 revealing that the cells of morula 2 would be segregated into ICM. One group (morula 1; 13/30 cells) showed the expression of genes highly expressed in TE, such as DAB2 and TEAD4, indicating the group of cells has been determined into TE lineage.…”
Section: Icm and Te Precursors In Porcine Morulamentioning
confidence: 99%
“…LncRNAs can be located in the nucleus or cytoplasm, depending on the cell types and detection methods (Derrien et al, 2012; van Heesch et al, 2014). In oocytes or embryos, fluorescence in situ hybridization (FISH) showed that three lncRNAs were in the cytoplasm of bovine GV oocytes (Caballero et al, 2014), and lincGET was in the nucleus of two‐ to four‐cell mouse embryos (J. Wang et al, 2018). In the present study, we failed to position lncRNA2193 in porcine oocytes because the RNA probe synthesized for FISH could not work well.…”
Section: Discussionmentioning
confidence: 99%